Analisis Pengendalian Kualitas Tahu dengan Metode New Seven Tools di UD. Graha Sukses Desa Pungka - Mashabai, Ismi; Utami, Rani Nur; Utami, Silvia Firda; Ulfaturrahmi, Ulfaturrahmi (Fakultas Teknik Universitas Tulang Bawang, 2025)
UD Tofu Factory. Graha Sukses produces tofu, the results of observations in the field, there are tofu defects. The new seven tools method is seven tools that are able to explore data qualitatively. Affinity Diagram, Interrelationship, Tree diagram is the human factor, lack of caution in the printing process. Machine, manual printing tool. Environment, product storage location is less tidy and hot. Materials, less checked before processing. Methods, SOPs of printing equipment and printing processes are not paid attention to. Matrix diagrams, supervision of soaking, molding and moving products score 9 and training to workers related to SOPs and product quality score 8. Matrix data analysis, priority score of improvement proposals 3, improvement in UD paying attention to SOP score 2, training to workers score 2, supervision of workers score 2, scheduling maintenance of tools score 2, changing manual tools to automatic score 2, making checksheets score 2, checking raw materials before and after production score 2. The arrow chart of the critical path is the A-C-E-G path. PDPC diagram proposes improvements by conducting training to workers for SOPs, check sheets are used to recap defective products and checking materials before use. Keywords: Disabled tofu, New seven tools, UD. Graha Sukses